Secondary Magnetic Reconnection at Earth’s Flank Magnetopause - Tang, B. B.; Li, W. Y.; Wang, C.; Khotyaintsev, Yu. V.; Graham, D. B.; Zhang, Q. H.; Sun, T. R.; Li, H.; Wang, X. Y.; Trattner, K. J.; Giles, B. L.; Lindqvist, P. A.; et al. (Frontiers in Astronomy and Space Sciences, 2021)
We report local secondary magnetic reconnection at Earth's flank magnetopause using the Magnetospheric Multiscale (MMS) mission. This reconnection is found at the magnetopause boundary with a large magnetic shear between closed magnetospheric field lines and the open field lines generated by the primary magnetopause reconnection at large scales. Evidence of this secondary reconnection are presented, which include a secondary ion jet and the encounter of the electron diffusion region. Thus the observed secondary reconnection indicates a cross-scale process from a global scale to an electron scale. As the aurora brightening is also observed at the morning ionosphere, the present secondary reconnection suggests a new pathway for the entry of the solar wind into geospace, providing an important modification to the classic Dungey cycle.